The Effect Of Service Quality And Effective Communication On The Level Of Satisfaction Of Service Users At The Blood Transfusion Unit Of The Oku Timur Regional General Hospital In 2025 - Lestari, Indah Putri; Rumengan, Grace; Ulfa, Laila; Agustin, Dinni (Journal of Ageing And Family, 2024)
The background of this research is the demand of the community in public services where hospitals must provide quality services according to the needs and desires of patients while still referring to the professional and medical code of ethics. The purpose of this study is to analyze the influence of service quality and effective communication on the level of satisfaction of blood service users at the East OKU Hospital. This study is a quantitative study with a cross sectional design. Data was collected through a questionnaire to 206 blood service users at UTD East OKU Hospital in January 2025 using accidental sampling techniques. Data analysis was carried out by linear regression test. The results showed that service quality partially had a positive and significant effect (t-Count 10,306) on service user satisfaction and effective communication partially had a positive and significant effect (t-Count 2,604) on service user satisfaction. The quality of service and effective communication simultaneously had a positive and significant effect on the satisfaction of service users (F count 108.963) where the quality of service had a greater influence on satisfaction. The conclusion of this study is that the respondents' perception good satisfaction, good service quality, and very good effective communication. Improvements are needed in the cleanliness and comfort of facilities, waiting rooms, buildings and the environment as well as the attitude and communication of officers. Inhouse Training Hospital Service Excellent, Internal/External Quality Control and evaluation of other factors such as product quality, cost and customer sentiment can be an effort to improve service and satisfaction. Keywords: Service quality, effective communication, satisfaction.